Health Monitoring of Closure Joints in Accelerated Bridge Construction: A Review of Non-Destructive Testing Application - Farhangdoust, Saman; Mehrabi, Armin (Journal of Advanced Concrete Technology, 2019)
Accelerated Bridge Construction (ABC) uses prefabricated elements that are made continuous using cast-in-place joints. Deck joints are normally referred to as “Closure Joints.” There have been concerns about long-term durability of these joints that are expected to become rapidly serviceable. Normally, they contain reinforcing bars and enclosures of various shapes that in some cases create congestion within the joint. The specific nature of the joint application, in-situ casting, curing, material incompatibility, cold joints, cavities and steel congestion contribute to creating the potential for leaving defects and anomalies in the closure joints. This, in turn, results in a higher potential for exposure and other detrimental effects with possible degradation in time, and therefore reducing the strength and serviceability of the joint, hence creating a weak link for the structure. The long-term deflections and environmental loading will only exacerbate the situation. Hence, evaluation and health monitoring of the closure joints becomes inevitable. Despite the wide use of non-destructive testing (NDT) methods for bridge structures in general, a concerted attempt for categorization of these methods, comparison of capabilities, and selection of methods most applicable to closure joints is lacking. To address this, a research project was carried out as part of activities in the Accelerated Bridge Construction University Transportation Center (ABC-UTC) of Florida International University. This study included a comprehensive literature review with a focus on NDT methods applicable to health monitoring of ABC closure joints. The study focused on joint types relevant to precast concrete decks commonly used for ABC bridges, therefore, FRP (fiber reinforced plastic), timber (wood), and steel of any shape were excluded for the time being. The study resulted in categorizing the most common closure joints in five general groups based on their features affecting the application of the NDT methods. Accordingly, the most promising NDT methods were identified taking into account the distinctive defects and anomalies associated with closure joints. These methods were evaluated for their efficacy, ease of use and other characteristic influencing their use as preferred methods for each type of joint. A flowchart was introduced to assist in selection of the most applicable NDT method to each type of defect in closure joints. This paper summarizes the results of this study.